Workers’ compensation claims for precariously employed workers in Ontario: employer resistance and workers’ limited voice - MacEachen, Ellen; Senthanar, Sonja; Lippel, Katherine (Perspectives interdisciplinaires sur le travail et la santé, 2021)
The policies and practices of workers’ compensation have barely kept pace with the changing worker and employer needs created by the growth of precarious forms of employment. This study focused on how well workers’ compensation and RTW policies in Ontario fit the needs of precariously employed workers. A critical discourse analysis guided our study which consisted of in-depth interviews with 15 precariously-employed workers and 5 employers who had hired and managed these kinds of workers. Three domains where RTW policies fit uneasily with the experiences of precariously-employed workers were identified. These related to knowledge and power contrasts between well-informed employers and vulnerable workers, injury attribution challenges, and worker fear of speaking up about accidents. This study suggests that workers’ compensation and RTW policies rest uneasily with the circumstances of precariously-employed workers. In particular, it was difficult for workers to engage with/make a claim for workers’ compensation when employers resisted this process.